Pemphigus Vulgaris and its Comprehensive Management: Report of Two Cases and Literature Review - Boza Oreamuno, Yadira V.; González Quesada, Jorge (Odovtos - International Journal of Dental Sciences, 2021)
In the oral cavity, gingiva lesions may occur that are not associated with bacterial plaque, which require adequate diagnosis and treatment. Desquamative gingivitis is usually related to mucocutaneous disorders, such as pemphigus vulgaris (PV), where oral lesions, including gingival lesions, may precede skin lesions. Management is multidisciplinary and treatment includes topical and systemic pharmacological therapy, require adequate control of dental plaque by the patient and strict supervision over time by the professional for the maintenance and stability of the gingival tissues. Two clinical cases of patients with a diagnosis of PV are presented, which were managed in a timely and integral way to control and stabilize the systemic and local factor.